2013
DOI: 10.1186/1465-9921-14-108
|View full text |Cite
|
Sign up to set email alerts
|

Conditional over-expression of RAGE by embryonic alveolar epithelium compromises the respiratory membrane and impairs endothelial cell differentiation

Abstract: BackgroundReceptors for advanced glycation end-products (RAGE) are cell surface receptors prominently expressed by lung epithelium. Previous research demonstrated that over-expression of RAGE by murine alveolar epithelial cells during embryogenesis caused severe lung hypoplasia and neonatal lethality. However, the effects of RAGE over-expression on adjacent matrix and endothelial cells remained unknown.MethodsRAGE transgenic (TG) mice were generated that conditionally over-expressed RAGE in alveolar type II ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…RAGE is expressed highly on alveolar type-I (AT-I) cells under normal conditions [ 19 , 40 ] serving as a marker of terminal differentiation on these cells [ 15 ]; hence the absence of RAGE may contribute to defective differentiation of the alveolar epithelial cells lining the lung parenchyma. In fact, transgenic mice that over-express RAGE in SP-C expressing alveolar type—II epithelial cells displayed significant alveolar hypoplasia, alterations in alveolar differentiation and weakened basement membrane [ 41 , 42 ]. In addition mouse models that over-express RAGE have poor alveolar septation during post-natal development [ 33 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAGE is expressed highly on alveolar type-I (AT-I) cells under normal conditions [ 19 , 40 ] serving as a marker of terminal differentiation on these cells [ 15 ]; hence the absence of RAGE may contribute to defective differentiation of the alveolar epithelial cells lining the lung parenchyma. In fact, transgenic mice that over-express RAGE in SP-C expressing alveolar type—II epithelial cells displayed significant alveolar hypoplasia, alterations in alveolar differentiation and weakened basement membrane [ 41 , 42 ]. In addition mouse models that over-express RAGE have poor alveolar septation during post-natal development [ 33 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 The receptor for advanced glycation end products (RAGE) is a pattern recognition and danger signal receptor that is most abundantly expressed in the lungs 18,19 and contributes to lung physiology. 20,21 RAGE is a driving force of inflammation in both patients with nonpulmonary [22][23][24][25][26][27] and those with pulmonary [28][29][30][31] diseases. Human genome-wide association studies have identified sequence variants in the gene for RAGE (AGER), which are associated with decreased FEV 1 , a key respiratory parameter impaired in asthmatic patients.…”
mentioning
confidence: 99%
“…RAGE is a cell-surface membrane protein of the immunoglobulin superfamily expressed by many cell types including endothelial and vascular smooth muscle cells, fibroblasts, macrophages/monocytes, and epithelium (3,40). RAGE is purported to play an important role in intracellular signaling observed during the coordination of developmental tasks such as cell spreading and adherence during organ formation (46). Following organogenesis, however, RAGE expression persists at the basolateral membrane of differentiated alveolar epithelial cells, where it influences interactions with the extracellular matrix and may contribute to structural and apoptotic changes associated with alveolar epithelial cell maintenance (8,38).…”
mentioning
confidence: 99%